Perception of The Islamic Banks Toward The Qardhul Hasan Products In Indonesia - Prasetyowati, Riris Aishah (Jurnal Manajemen, 2018)
This research study deals with the perceptions of customers of Islamic Banks on the issue of Qardhul Hasan in Indonesia. The study adopted the methodology of questionnaire survey. 15 full-fledged Islamic banks in Indonesia are used in the study. The response rate is 46,9% . The findings are divided into three sections : Knowledge and awareness about Qardhul hasan, General Information on Qardhul hasan, Problems and obstacles of Qardhul Hasan in Islamic banks and differences in Perceptions and behaviors among customers of the Islamic Banks on the issue of Qardhul Hasan. In general, the Islamic banks are familiar with Qardhul hasan and they agreed that Islamic banks should offer Qardhul hasan in order to enhance corporate social responsibility and to help needy people. Therefore, the findings could provide insights to Islamic banks in diversifying their products by offering qardhul hasan to the customers but with proper guidelines and policies.